Modulation of Nutritional and Biochemical Properties of Wheat Grains Infected by Blast Fungus Magnaporthe oryzae Triticum Pathotype - Surovy, Musrat Zahan; Mahmud, Nur Uddin; Bhattacharjee, Pallab; Hossain, Md. Shaid; Mehebub, Md. Shabab; Rahman, Mosaddiqur; Majumdar, Bhaskar Chandra; Gupta, Dipali Rani; Islam, Tofazzal (Frontiers in Microbiology, 2020)
Wheat blast disease caused by the Magnaporthe oryzae Triticum (MoT) pathotype exerts a significant impact on grain development, yield and quality of the wheat. The aim of this study was to investigate morphological, physiological, biochemical and nutritional properties of wheat cv. BARI Gom 24 under varying levels of blast disease severity in wheat spikes. Grain morphology, volume, weight and germination of the infected grains were significantly affected by MoT. Biochemical traits specifically grain N, Ca, Mg and Fe content significantly increased (up to 3-fold) (p>0.05), but organic carbon, Cu, Zn, B, and S content in wheat grains significantly decreased with increased severity of MoT infection. The grain crude protein content was about 2-fold higher (up to 18.5% in grain) 26 in severely blast infected grains compared to the uninfected wheat one (9.7%). Analysis of other nutritional properties such as secondary metabolites revealed that total antioxidant activity, flavonoid and carotenoid concentrations remarkably decreased (up to 3-fold) with increasing severity of blast infestation in wheat grain. Grain moisture, lipid, and ash content were slightly increased with the increase of blast severity. However, grain K and total phenolic concentration were increased at a certain level of blast infestation and then reduced with increase of MoT infestation.